Making Use of Ispring Suite Media in Learning Science in Junior High Schools - Muslan Muslan; Piyada Kaewkanlaya; M. Yakub Iskandar; Abna Hidayati; La Mai Tulum; Affifah Zurida Sya'bani; Quratul Akyuni (International Journal of Multidisciplinary Research of Higher Education, 2023)
The study is aimed at designing and analyzing the product validity of learning media of Ispring Suite used for science class in Junior High School. The study employs the Research & Development method of Borg and Gall consisting of five stages namely; planning, design, validation, revision and final product. Powerpoint and Ispring Suite are used in designing the product. further, the validity of the product is assessed by two experts in media learning for science. Based on the findings it can be concluded that the product is feasible and qualified to be applied in science class in Junior High Schools. Last, the product can be effectively used after it is downloaded in playstore, marketplace or google market. The researcher recommends that future researchers increase the number of studies related to the development of media products for science learning, so that the products that have been produced can be integrated by science teachers in learning.